2015
DOI: 10.7243/2052-935x-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal childhood abuse history on child’s attachment problems

Abstract: Background: The aim of this study was to investigate the independent impact of maternal childhood abuse history (MCAH), after controlling for maternal past, current parenting, and paternal past parenting, and maternal mental health (MMH) on the attachment problems of children living in mother-child homes in Japan. Methods: A self-administered questionnaire survey was conducted among mothers (N=306) staying in 83 mother-child homes in Japan to assess mothers' and fathers' maltreatment toward their children befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(33 reference statements)
0
0
1
Order By: Relevance
“…We found no effect of maternal history of ELM on child HRQoL even though previous research has shown that ELM poses a general risk factor for child functioning in terms of psychiatric and attachment problems (Bosquet Enlow et al, 2016;Mizuki et al, 2015). We conclude that maternal history of ELM has differential effects on distinct aspects of health as defined by the WHO (1948): Maternal ELM may not affect children's subjective experience of well-being even though it poses a higher risk for psychopathology.…”
Section: Impact Of Maternal History Of Elm and Depression On Child Quality Of Lifecontrasting
confidence: 60%
“…We found no effect of maternal history of ELM on child HRQoL even though previous research has shown that ELM poses a general risk factor for child functioning in terms of psychiatric and attachment problems (Bosquet Enlow et al, 2016;Mizuki et al, 2015). We conclude that maternal history of ELM has differential effects on distinct aspects of health as defined by the WHO (1948): Maternal ELM may not affect children's subjective experience of well-being even though it poses a higher risk for psychopathology.…”
Section: Impact Of Maternal History Of Elm and Depression On Child Quality Of Lifecontrasting
confidence: 60%